Reading fear in Flavian epic emotion, power and stoicism - Agri, Dalida ca. 20./21. Jh (Oxford University Press, 2022)
Notes on Texts and Abbreviations -- Introduction -- 0.1 Outline, Context, and Approach -- 0.2 Ancient Interactions Between Poetry and Philosophy -- 0.3 Scholarship on Emotions and Stoic Influences in Flavian Epic -- 0.4 Stoic Views on Emotion -- 0.5 What Is an Emotion? The Greek Stoic Legacy in Roman Thought -- 0.6 Seneca on Poetry -- 0.7 Stoics Views on Kingship and Tyranny -- 0.8 The So-called 'Stoic Opposition' -- 0.9 The Tyrant in the Poetic Tradition -- 0.10 Structure of the Argument -- 1. Fear in Flavian Representations of Epic Tyrants: Depictions and Uses of Emotion -- 1.1 Valerius Flaccus' Argonautica: King Pelias -- 1.1.1 Statius' Thebaid: Polynices -- 1.1.2 Statius' Thebaid: King Creon -- 1.2 Silius Italicus' Punica: Hannibal -- 2. Reading Fear in Valerius Flaccus' Argonautica -- 2.1 Fear and Hope -- 2.2 Fear and Prophecy -- 2.3 Fear, Divine Will, and Human Agency -- 2.4 Medea: Between Power and Vulnerability -- 2.4.1 The Proserpina Simile -- 2.4.2 Fear and the Female Body -- 2.4.3 Stoic Resistance? -- 2.4.4 Reverse Sex Similes -- 3. Reading Fear in Statius' Thebaid -- 3.1 Tisiphone or the Incarnation of the Passions -- 3.2 Fear as a Political Idea -- 3.3 Fear, Power, and Agency -- 4. Reading Fear in Silius Italicus' Punica -- 4.1 Rome on Carthage: The 'War on Terror' -- 4.2 Fear, cupido gloriae, and the Horse Analogy -- 4.3 Carthage, Tyranny, and 'the Fear Within' -- Epilogue -- Bibliography -- Index Locorum -- General Index
This book examines the textual representations of emotions, fear in particular, through the lens of Stoic thought and their impact on depictions of power, gender, and agency. It first draws attention to the role and significance of fear, and cognate emotions, in the tyrant's psyche, and then goes on to explore how these emotions, in turn, shape the wider narratives. The focus is on the lengthy epics of Valerius Flaccus' Argonautica, Statius' Thebaid, and Silius Italicus' Punica. All three poems are obsessed with men in power with no power over themselves, a marked concern that carries a strong Senecan fingerprint. Seneca's influence on post-Neronian epic discourse can be felt beyond his plays. His Epistles and other prose works prove particularly illuminating for each of the poet's gendered treatment of the relationship between power and emotion. By adopting a Roman Stoic perspective, both philosophical and cultural, this study brings together a cluster of major ideas to draw meaningful connections and unlock new readings
Keywords: Flavier -- Dynastie : 69-96; Geschichte 50-100; Epos; Latein; Literatur; Angst -- Motiv; Epic poetry, Latin / History and criticism; Fear in literature; Epic poetry, Latin; Classical philology; Latin poetry; Flavian family; Electronic books